Fundamentals of Propulsion - Babu, V.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This highly informative book offers a comprehensive overview of the fundamentals of propulsion. The book focuses on foundational topics in propulsion, namely gas dynamics, turbomachinery, and combustion to more complex subjects such as practical design aspects of aircraft engines and thermodynamic aspects and analysis. It also includes pedagogical aspects such as end-of-chapter problems and worked examples to augment learning and self-testing. This book is a useful reference for students in the area of mechanical and aerospace engineering. Also, scientists and engineers working in the areas of aerospace propulsion and gas dynamics find this book a valuable addition.
Introduction -- Basics of Compressible One Dimensional Flows -- Basics of Turbomachinery -- Basics of Combustion Thermodynamics -- The Turbojet Engine -- The Turbofan Engine -- Thrust Calculations -- Ramjet and Scramjet Engine.
Keywords: Engines; Aerospace engineering; Astronautics; Electric power production; Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Engine Technology; Aerospace Technology and Astronautics; Mechanical Power Engineering; Engineering Thermodynamics, Heat and Mass Transfer; Aerodynamics; Propulsion systems